OP09 Assessing models of ACP in primary care, the meta-LARC trial: part 3 theory-based design of an interprofessional team training. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Totten, A; Caron, D; Izumi, S; Guay-Belanger, S; Legare, F
Abstract : Background and aims: Implementing advance care planning (ACP) in primary care practice has been challenging. An approach incorporating interprofessional (IP) team members has potential to facilitate ACP conversations though teams may lack ACP training. We adapted and pilot tested a program to train IP teams in ACP. Methods: We developed an ACP conversation training program for primary care teams by adapting the Serious Illness Care Program by Ariadne Labs and incorporating the Interprofessional Approach to Shared Decision Making Model. The training materials were reviewed by eight health professionals and three patient and family advisors for acceptability and feasibility, then pilot tested with six interdisciplinary members of a primary care team. Reviewers' comments and post training interviews were analyzed using qualitative descriptive analysis methods. Results: The training program consists of a 1.5 hour online module and a 1.5 hour in-person interactive session. Reviewers' comments included: both concerns about and support for non-physician team members discussing prognosis; questions about how to share the responsibility/time for conversations; and need for communication within teams and with patient/families. Post pilot training interviews also revealed barriers to ACP, and lack of clarity about how to share and communicate the conversations across team members. We modified the training and created scenarios showing various team-based approaches for ACP. Conclusion: Initial assessment indicated the need to adapt ACP approaches for interprofessional team members. In the next step, we are testing the effectiveness of the modified IP ACP conversation training in primary care practices in the US and Canada.